Study and analysis of modified LMF control method for power quality improvement - Rajaboyana Narendra Rao; Meda Sreenivasulu; Busharaju Ramakrishna (International Journal of Power Electronics and Drive Systems (IJPEDS), 2023)
This paper presents a least fourth-based control method for distribution static compensator for compensation of power quality issues that are reactive power, issues of current, unbalancing loads. The direct current (DC) link voltage of distribution static compensator operated as self-supported. The control method used to extracting the tuned mass reactive and active power values of load values. They are significant divisions in source reference currents. The comparison of harmonic distraction with PI and PSO-PI controller is discussed. The proposed DSTATCOM is tested under nonlinear load condition and its working is seen as palatable. The proposed system is developed and simulated by utilizing MATLAB/Simulink with accessible sim power tool (SPS).